2017
DOI: 10.21276/aimdr.2017.3.4.rd5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasonography (USG) in Evaluation of Pericholecystic Adhesions in Gallstone Disease (GSD)

Abstract: Background: In the recent era of laparoscopic and robotic surgeries, preoperative imaging has become very crucial in selecting the right operative technique in any pathological condition. Though laparoscopic cholecystectomy is widely accepted and practiced surgical technique yet it has limitations especially dense pericholecystic adhesions where the surgeon requires larger field of view for optimal dissection of gall bladder bed and for optimal control of bleeding. Though ultrasonography has been in wide use f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Their study revealed that ultrasonography has more than 70% sensitivity, more than 80% specificity, and more than 76% accuracy in predicting pericholecystic adhesions which is the major cause of conversion from laparoscopic to open cholecystectomy. 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study revealed that ultrasonography has more than 70% sensitivity, more than 80% specificity, and more than 76% accuracy in predicting pericholecystic adhesions which is the major cause of conversion from laparoscopic to open cholecystectomy. 24…”
Section: Discussionmentioning
confidence: 99%
“…26 accuracy in predicting pericholecystic adhesions which is the major cause of conversion from laparoscopic to open cholecystectomy. 24 Only one study was conducted in children population that was conducted by Tan et al They assessed visceral sliding as a marker of visceroparietal adhesion. Their reported sensitivity and specificity in predicting adhesions were 75 and 80%, respectively.…”
Section: Fibrinous Exudates Uneven Hypoechoic Shadow 59mentioning
confidence: 99%